2012
DOI: 10.1371/journal.pone.0035782
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Persistence of Salmonella enterica Serotype Senftenberg Strains Could Explain the Emergence of this Serotype in Poultry Flocks

Abstract: Salmonella enterica serotype Senftenberg (S. Senftenberg) has recently become more frequent in poultry flocks. Moreover some strains have been implicated in severe clinical cases. To explain the causes of this emergence in farm animals, 134 S. Senftenberg isolates from hatcheries, poultry farms and human clinical cases were analyzed. Persistent and non-persistent strains were identified in chicks. The non-persistent strains disappeared from ceca a few weeks post inoculation. This lack of persistence could be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 36 publications
2
28
0
1
Order By: Relevance
“…Among the isolates, 153 (84%), 13 (7%), 6 (3%), 5 (3%), and 5 (3%) were isolated from humans, surface water, poultry, pork, and seafood, respectively. Previous studies have suggested that S. Senftenberg can contaminate food or water supplies (4,5). Molecular subtyping analysis showed that some isolates from food or water had a close relationship with the isolates from clinical patients.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Among the isolates, 153 (84%), 13 (7%), 6 (3%), 5 (3%), and 5 (3%) were isolated from humans, surface water, poultry, pork, and seafood, respectively. Previous studies have suggested that S. Senftenberg can contaminate food or water supplies (4,5). Molecular subtyping analysis showed that some isolates from food or water had a close relationship with the isolates from clinical patients.…”
Section: Discussionmentioning
confidence: 93%
“…In developed countries, NTS remains one of the leading causes of death among food-borne bacterial pathogen infections, and outbreaks are fairly common (2,3). Salmonella enterica serovar Senftenberg infections in humans have been associated with the consumption of poultry (4,5) and plant-derived food commodities (6). Although S. Senftenberg is an uncommon cause of human infections globally (7)(8)(9), including in China (10,11), increasing antimicrobial resistance supports the need for specific surveillance for this serotype (5,8).…”
mentioning
confidence: 99%
“…Senftenberg has also previously been reported as the cause of serious human infections (14)(15)(16). S. Senftenberg is well recognized as being common among poultry (17), but it has also been associated with infant formula (18), mussels (19), and vegetables (16,20,21). It is noteworthy that one of the patients claimed to have consumed vegetables prior to onset of symptoms.…”
mentioning
confidence: 95%
“…Senftenberg isolates are often associated with colonization of hatcheries and are gradually eliminated during animal rearing. However, S. Senftenberg isolates that are able to persist throughout the rearing period into adulthood have recently emerged (15), with these same isolates displaying resistance to desiccation in soil (16). Clinically, infections caused by S. Senftenberg range from asymptomatic (17,18) to severe infections resulting in large out-breaks (19,20).…”
mentioning
confidence: 99%